PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA MATERI PANAS DAN PERPINDAHANNYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD GMIT NAIONI KOTA KUPANG - Gaspar Melo; Andriyani A. D. Lehan; Petrus L. B. Loy (Universitas Nusa Cendana, 2023)
This study aims to determine the application of the Problem Based Learning (PBL) model in learning theme 6 sub-theme 2 learning 1 to improve student learning outcomes in class V SD GMIT NAIONI, Kupang city, academic year 2022/2023. This type of research is classroom action research carried out in two cycles. Each cycle consists of planning, implementation/action, observation/evaluation, and reflection stages. The subjects of this research were the fifth grade students of SD GMIT NAIONI, totaling 33 students. The collected data were analyzed using the test method. The data obtained from the test method was then analyzed using a quantitative descriptive technique. The results of this study indicate that in learning theme 6, sub-theme 2, learning 1 using the PBL model can improve learning outcomes for fifth grade students at SD GMIT NAIONI, Kupang City, in the 2022/2023 academic year. In the first cycle, the average student learning outcomes were 69.55% in the low category and increased to 80.00% in the second cycle, which was in the high category. so the Problem Based Learning model can improve student learning outcomes on theme 6 sub-themes 2 learning 1 class V SD GMIT NAIONI city of Kupang 2022/2023 academic year.